Síntese de N-dióxidos derivados de piperazinas e zidovudinas - Wendt, Marcelo (2022)
Chalcogenonucleosides has been the object on studies because of its biological potential and their pharmaceutical properties, with prominence antitumor, antiviral and antioxidant properties. In addition, piperazine structures are present in compounds of pharmacological application showing antimicrobial, anticancer, antidepressant properties, among others. Finally, compounds derived from 2H-benzimidazole N,N-dioxides, despite being less studied when compared to the previous classes, have shown results that point to their potential, being used as an antiparasitic agent, in addition to having antitumor and antioxidant properties.With this in mind, the present work sought to develop a synthetic methodology to obtain new compounds of 1-(aryl-sulfonyl)-4-(1,3-dioxide-2,2-dimethyl-2H-benzimidazole)-acetylpiperazines 3a-c and 5'-arylcalcogenyl-3'-(1,3-dioxide-2,2-dimethyl-2H-benzimidazo-amido)- thymidines 5a-m, in order to make it possible to obtain 16 new compounds through , using DCC and DCM in open atmosphere and at room temperature, with good yields (49% to 90%). Additionally, in silico and in vitro tests, it was found that the compounds obtained showed favorable molecular anchoring results for interaction with the active site of the main protease of SARS-CoV-2, as well as an inhibitory action against it, indicating the possibility of acting as an inhibitor of SARS-COV-2